Abdul Halim Hasan and his methodological approach in tafsir Al-Quran Al-Karim=Abdul Halim Hasan dan metodologinya dalam tafsir al-Quran al-Karim - Ahmad, Nadzrah (IIUM Press, 2017)
Abdul Halim Hasan was a Malay exegetical writer of Indonesian origin. His work on Qur’Énic exegesis, or tafsir, transcended geographical boundaries and reached audiences around the Malay regions, especially Malaysia. The academic value of this particular tafsir is undeniably outstanding as an early twentieth century exegetical writing. This paper highlights Abdul Halim Hasan and his academic measures in the writing of TafsÊr al-Quran al-Karim. Emphasis was given towards his biography and methodological contribution in tafsir. This qualitative study utilized deductive and inductive method to examine and discuss his tafsir as well as methodology. The result indicated that Abdul Halim Hasan implemented specific methodology in his tafsÊr, benefitting from his reference of the past scholars in this field.